Special education teachers’ job demands-resources profiles and capabilities: Effects on work engagement and intention to leave - Murangi, Annelisa; Rothmann, Sebastiaan; Nel, Mirna (Frontiers in Psychology, 2022)
This study aimed to investigate the job demands-resources profiles and work capabilities of special education teachers in Namibia and their effect on work engagement and intention to leave. A convenience sample was taken of teachers from seven different regions across Namibia (N = 200). The Capability Set for Work Questionnaire, the Job Demands-Resources Questionnaire, the Work Engagement Questionnaire, and the Intention to Leave Questionnaire were administered. Using latent profile analysis, four job demands-resources profiles were identified: resourceful job, demanding job, poor job, and rich job. A poor job was negatively associated with the capability to use knowledge and skills, while resourceful and rich jobs were associated with developing new knowledge and skills, being involved in important decisions, building and maintaining relationships, and setting own goals. Job experience was negatively associated with five of the seven capabilities. Resourceful and rich jobs and the capability set predicted a large percentage of the variance in work engagement and a moderate percentage of the variance in intention to leave. High emotional demands, coupled with overload and a lack of resources interfere with teachers’ functioning (e.g., work engagement and intention to leave).